Hope for bone regeneration: The versatility of iron oxide nanoparticles - Wang, Nan; Xie, Yimin; Xi, Zhipeng; Mi, Zehua; Deng, Rongrong; Liu, Xiyu; Kang, Ran; Liu, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Although bone tissue has the ability to heal itself, beyond a certain point, bone defects cannot rebuild themselves, and the challenge is how to promote bone tissue regeneration. Iron oxide nanoparticles (IONPs) are a magnetic material because of their excellent properties, which enable them to play an active role in bone regeneration. This paper reviews the application of IONPs in bone tissue regeneration in recent years, and outlines the mechanisms of IONPs in bone tissue regeneration in detail based on the physicochemical properties, structural characteristics and safety of IONPs. In addition, a bibliometric approach has been used to analyze the hot spots and trends in the field in order to identify future directions. The results demonstrate that IONPs are increasingly being investigated in bone regeneration, from the initial use as magnetic resonance imaging (MRI) contrast agents to later drug delivery vehicles, cell labeling, and now in combination with stem cells (SCs) composite scaffolds. In conclusion, based on the current research and deveiopment trends, it is more inclined to use in bone tissue engineering, scaffolds, and composite scaffolds.